Pengaruh Green Accounting dan Capital Structure terhadap Financial Performance dengan Firm Debt sebagai Variabel Moderasi - Maritza, Syarah; Wenten, I Ketut (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to test and analyze the influence of green accounting and capital structure on financial performance which is moderated by firm debt. The analysis was carried out using annual reports of companies listed in the Industrial sector on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The samples used in this research were 9 samples of Industrial companies obtained using the purposive sampling technique using the following criteria. which has been set. The data used is secondary data in the form of annual reports of public companies published on the Indonesia Stock Exchange (BEI) website and the company's official website. This research uses 2 independen variabels, namely green accounting (X1) and capital structure (X2) with a dependent variabel, namely financial performance (Y), and a moderating variabel, namely firm debt (Z). This research uses the panel data regression as an analysis technique which is carried out using the E-Views 12 Student Version Lite software. The research results showed that green accounting and capital structure simultaneously influence financial performance. Green accounting partially did not have any effect on financial performance, capital structure partially has an effect on financial performance. Firm debt was not able to moderate the influence of green accounting on financial performance, firm debt was able moderate the influence of capital structure on financial performance.